Next generation leadership : how to ensure young talent will thrive with your organization - Kingl, Adam ([New York] : HarperCollins Leadership, an imprint of HarperCollins, 2020)
Employers who refuse to adapt to the expectations of younger generations are losing out on top talent, as they leave for positions at companies with more modern practices. Learn what companies need to do to fit into the new normal in the workplace.
Includes bibliographical references (pages 175-196) and index.
Keywords: Generation Y -- Employment; Personnel management; Conflict of generations in the workplace